ANALYSIS OF AERODYNAMIC PERFORMANCE OF EROSION AIRFOIL WITH REYNOLDS NUMBER VARIATIONS - James Julian; Waridho Iskandar; Fitri Wahyuni (Jurnal Ilmiah Teknologi dan Rekayasa, 2023)
Erosion on airfoil was investigated using computational methods to investigate changes in the performance of the airfoil. NACA 0015 used in this study has a chord length of 1 m, which is then used as a parameter in calculating the Reynolds number. The computational process is carried out with domain C with dimensions that have been arranged in such a way as to avoid the influence of the boundary on the computational results obtained in this study. The governing equation for this study is RANS which the standard k-ω turbulence model supports. Erosion has a considerable influence on changes in the aerodynamic performance of the airfoil. Erosion can significantly reduce the Cl value of the airfoil, especially at high AoA. Erosion of the airfoil results in an increase in the value of Cd. The increase in Cl value can be explained by visualizing the pressure contour around the airfoil. The pressure contour shows a decrease in pressure in the lower but an increase in the upper. The velocity and streamline contours can explain the cause of the increase in Cd, which is very clearly caused by the separation in the erosion area and on the upper surface of the airfoil.